The effects of an 8-week unilateral plyometric training program on jump performance, change of direction, and interlimb asymmetries in ice hockey players - Moreno-Azze, A.; López-Plaza, D.; Falcón-Miguel, D.; Gómez-Carmona, C. D. (The Journal of Strength and Conditioning Research, 2026)
This study aimed to investigate the effects of an 8-week unilateral plyometric training program on lower limb performance, interlimb asymmetries, and change-of-direction (COD) abilities in male and female ice hockey players. Twenty-nine ice hockey players (15 men, 14 women) were first divided by sex and then assigned to experimental (EG) and control (CG) groups. The EG underwent a unilateral plyometric training program apart from their regular training, while the CG maintained only their regular training. Functional performance tests, including single-leg hop (SH), triple hop (TH), countermovement jump (CMJ), and COD tests on both track and ice surfaces, were conducted preintervention and postintervention. The EG showed significant improvements in jump performance and COD, with reductions in interlimb asymmetries. In particular, women of the EG demonstrated significant gains in SH (stronger leg: effect size [ES] = 1.20, p < 0.01; weaker leg: ES = 1.12, p < 0.01) and TH (stronger leg: ES = 1.18, p < 0.01; weaker leg: ES = 0.82, p = 0.02), while men improved in CMJ (stronger leg: ES = 0.54, p = 0.02), SH (stronger leg: ES = 1.42, p < 0.01; weaker leg: ES =1.26, p < 0.01), and COD (stronger leg: ES = 0.78, p = 0.05; weaker leg: ES = 0.69, p = 0.02). Asymmetry reductions were notable in SH for women (ES = -0.50, p < 0.01) and COD for men (ES = -0.76, p = 0.01). Unilateral plyometric training effectively enhances lower limb performance and reduces interlimb asymmetries in ice hockey players, with sex-specific adaptations.